2015
DOI: 10.1007/s10840-015-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intracardiac echocardiography during pulmonary vein isolation with the novel multipolar irrigated ablation catheter (nMARQTM)

Abstract: ICE might be a useful tool to guide nMARQ(TM) catheter position in the left atrium during atrial fibrillation (AF) ablation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The significant reduction in fluoroscopy time demonstrated in the main analysis was robust in all sensitivity testing, including studies with only AF patients (Hedges' g −1.25; 95% CI −2.14 to −0.36; P < .01) 10,11,24,26–31,37,38 . (Table S3).…”
Section: Resultsmentioning
confidence: 78%
“…Ten studies reported fluoroscopy dose data, with significant heterogeneity among studies (I 2 = 93%) and no evidence of publication bias or small study effects 23–28,31,33,37,38 . Use of ICE in ablation procedures showed significant reductions in fluoroscopy dose vs ablation without the use of ICE (Hedges' g −1.27; 95% CI −1.91 to −0.62; P < .01) (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies freedom from AF rate has been reported between 61% and 83% without procedure-related complications [4], [5], [25]. Similarly, with the nMARQ ® ablation the reported ranges for the mean procedural and fluoroscopy times were 69–160 min and 2–31 min, respectively [7], [24], [26], [27]. With a single procedure, freedom from arrhythmia recurrence has been reported between 65% and 81% [11], [28], [29].…”
Section: Discussionmentioning
confidence: 88%